Effective School Strategies in Developing the Competence of School Administrative Staff to Achieve Educational Vision - Sa'diyah, Ikrinatus; Ulfatin, Nurul; Nurabadi, Ahmad (Proceedings Series of Educational Studies, 2024)
This article aims to explore and analyze effective strategies implemented by schools in developing the competencies of administrative staff to support the achievement of educational vision. The competencies of administrative staff play a crucial role in ensuring the smooth operation of schools and making a tangible contribution to the success of educational programs. This research uses a qualitative approach with a literature method on books, journals, and previous sources. The research results indicate that several key strategies, such as relevant and ongoing training, the utilization of information technology, strengthening internal communication, and providing career development pathways, have proven effective in enhancing the performance of administrative staff. In addition, the proactive involvement of school management and consistent government policy support are considered very important for the success of competency development programs. This finding is expected to provide insights for education stakeholders in designing human resource development policies within the school environment.